Analisis Perubahan Zona Agroklimatologi Berdasarkan Klasifikasi Oldeman dan Implikasinya Terhadap Pengembangan Komoditas Hortikultura Utama di Kabupaten Lampung Selatan - Onny Chrisna Pandu Pradana; Sekar Utami Putri; Vinni Aurelia Salsabila; Ria Putri; Anna Dwi Putri (Journal of Horticulture Production Technology, 2026)
The agricultural sector is currently facing climate change as one of the foremost global challenges. Horticultural crops represent one of the agricultural subsectors most sensitive to such changes, particularly in terms of rainfall distribution, air temperature, water availability, relative humidity, and solar radiation intensity. The agroclimatological zone concept can be applied to determine the level of crop suitability relative to its growing environment, with the aim of stabilizing or even increasing crop productivity. One of the major horticultural crop centers in Lampung Province is South Lampung Regency. This study aims to (1) analysis the agroclimatological zones of South Lampung Regency over the past 16 years, (2) analysis the rainfall conditions and climate types in the South Lampung Regency area, and (3) analysis the suitability of agroclimatic zones in South Lampung for major horticultural commodities. The results of this study indicate that (1) shifts in agroclimatological zones have occurred in South Lampung Regency over the past 16 years, (2) South Lampung Regency shows a tendency toward increasingly arid conditions, as indicated by a climate type shift from C3 to D3, and (3) the South Lampung area remains suitable for the cultivation of primary horticultural commodities such as chili, eggplant, water spinach, and ginger, provided that planting and harvesting schedules are carefully aligned with the occurrence of wet and dry months.